Free Trade Reimagined : The World Division of Labor and the Method of Economics - Unger, Roberto Mangabeira (Book collections on Project MUSE., 2007)
Free Trade Reimagined begins with a sustained criticism of the heart of the emerging world economy, the theory and practice of free trade. Roberto Mangabeira Unger does not, however, defend protectionism against free trade. Instead, he attacks and revises the terms on which the traditional debate between free traders and protectionists has been joined. Unger's intervention in this major contemporary debate serves as a point of departure for a proposal to rethink the basic ideas with which we explain economic activity. He suggests, by example as well as by theory, a way of understanding contemporary economies that is both more realistic and more revealing of hidden possibilities for transformation than are the established forms of economics.